Japan As Number One: Lessons for AmericaVogelEzra F. Japan As Number One: Lessons for America. New York: Harper Colophon, 1979, 260 pp., $4.95 paperback. - Duncan, W. Jack (Academy of Management Review, 1981)
The article reviews the book ?Japan As Number One: Lessons for America,? by Ezra F. Vogel.